Dissonance-based Program for Eating Disorders Prevention in Mexican University Students - Claudia Unikel-Santoncini; Concepción Díaz de León-Vázquez; José Alberto Rivera-Márquez; Ietza Bojorquez-Chapela; Enrique Méndez-Ríos (Psychosocial Intervention, 2019)

(untitled)
The purpose of this study was to identify changes in the risk of eating disorders after a one-year follow-up of a dissonance-based eating disorders prevention program. The Body Project was implemented in a sample of male and female university students: 133, 110, and 74 at baseline, post-test, and follow-up respectively, and we tested the change in disordered eating behaviors (DEB) over time, and by levels of variables that according to the theoretical model lie on the path between the intervention and DEB, with one-way MANOVA analyses of repeated measures for the associations between internalization of the esthetic thin ideal, depressive symptoms, and DEB. The average value of DEB was 5.23 at pre-test, 3.45 at post-test, and 2.80 at follow-up. The model with DEB at each time point, as dependent variables, and internalization of the esthetic thin ideal and depressive symptoms, as independent variables, showed a significant effect of internalization of the esthetic thin ideal, F(2, 136) = 7.66, p = .0011, while there was no significant effect of depressive symptoms, F(2, 136) = 0.45, p = .6191, indicating that the intervention exerted its effect on DEB via the former variable. The intervention proved to produce effects after a one-year follow-up. These findings support the implementation of universal prevention programs using dissonance-based techniques.